Estudo do efeito dos diferentes tipos de cimento Portland nacionais na resistência à compressão do UHPC - Kronbauer, Ana Claudia (2019)
UHPC (Ultra high performance concrete) refers to a specific concrete composed by cement, silica fume, quartz sand, water and other additives that due to its particles being tightly packed, it achieves higher resistances than conventional concrete, in addition to being more durable due to its low permeability. Research on the behavior of high-performance concrete materials reveal the importance of studying the influence of their mechanical properties and according to the literature, the chemical composition as well as the thickness of the cement are factors that influence directly on the concrete mechanical strength. In order to analyze the influence of the main types of Portland cement on the mechanical properties of ultra-high performance concrete, different types of national cement were analyzed regarding their physical and che-mical characteristics and afterwards, they were used for the molding of UHPC test specimens in order to analyze their effects on the compressive strength of this concrete. The influence of the cement chemical composition on the concrete mechanical performance was analyzed. After a statistical analysis by the single factor ANOVA test, it was concluded that the cement type does not influence significantly on the UHPC mechanical performance. However, the CPV ARI presented the highest average compressive strength compared to the other cements. This fact corroborates with the literature that looks for a cement with greater specific surface area for the manufacture of UHPC.